Efektivitas Program BPJS Dalam Meningkatkan Akses Layanan Kesehatan Dan Kualitas Hidup Masyarakat di Surabaya: Tantangan dan Upaya Perbaikan - Nurany, Fierda; Wulandari, Tri Anggarani; Safrina Alya, Azwa; Nasa Salsabila, Niqma; Septiana Putri, Rafika (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Wiraraja, Sumenep, 2024)
The purpose of this study is to find out the meaning of online media audiences about Instagram. The role of mass media communication technology is developing rapidly and playing an important role for society in everyday life. The internet is very helpful in the field of marketing (online marketers). One form of online promotion that is currently developing is via Instagram, based on the photo sharing append commonly found on smartphones. As a start-up business company, the Instagram application has emerged, because of the internet phenomenon that has emerged recently, many new products have been marketed. For this reason, this paper can define how to share photos based on the Instagram application, especially for people who respond to start-up business promotions